A Permanent Research Platform for Ecological Studies in Intact Temperate Mountainous Forests from Slătioara UNESCO Site and Its Surroundings, Romania - Duduman, Gabriel; Duduman, Mihai-Leonard; Avăcăriței, Daniel; Barnoaiea, Ionuț; Barbu, Cătălina-Oana; Ciornei, Ioan; Clinovschi, Florin; Coșofreț, Vasile Cosmin; Cotos, Mihai-Gabriel; Dănilă, Gabriel; Dănilă, Iulian-Constantin; Drăgoi, Marian; et al. (Forests, 2020)
This paper describes a permanent research platform (PRP) designed and implemented in “Codrul secular Slătioara” and its surroundings (2205.85 ha), having also the role of introductory paper for future research articles based on data collected from this platform. “Codrul secular Slătioara” is known as one of the largest temperate mountainous intact forests of Europe and, in 2017, it was included in UNESCO World Heritage List, as part of the “Ancient and Primeval Beech Forests of the Carpathians and Other Regions of Europe”. Moreover, the PRP overlaps other three scientific reserves, the share of strictly protected forests exceeding 70%. This platform has a multiple role, being developed for research, conservation and educational activities. The PRP was designed for an ecological analysis of the intact forest ecosystems. It contains 193 circular sample plots, each of them of 500 m2, and it is structured on two levels. The first level contains 58 sample plots corresponding to a square grid of 500 × 500 m, stretching over the entire forested area, and the second level contains 135 plots, placed according to a square grid of 100 × 100 m, covering 136 ha within the core area of the UNESCO site. We measured the characteristics of 8296 living trees, 1743 standing dead trees, 1900 dead wood trunks, 3214 saplings, and the abundance–dominance indices of flora species. Thus, we identified 14 tree species, 17 shrub species, and 248 other cormophyte species forming the herbaceous layer. In terms of volume, the main tree species are Norway spruce, silver fir and European beech. The tallest species are Norway spruce (56 m) and silver fir (51 m). The average volume of living trees is 659 m3·ha−1, with a maximum of 1441 m3·ha−1. The mean total dead wood volume is about 158 m3·ha−1, with sample plots where the total dead wood volume exceeds 600 m3·ha−1. After presenting the results of preliminary data processing, the paper describes the main research topics to be further considered, based on the PRP, and the foresights related to the PRP’s monitoring and development.